Identifikasi Zona Rawan Longsor Menggunakan Metode Geolistrik Resistivitas Di Desa Pao Kecamatan Tombolo Pao Kabupaten Gowa - Muh. Adrian; L., Muh. Said; Fitriyanti (JFT: Jurnal Fisika dan Terapannya, 2023)
This research aims to identify landslide-prone zones using the geoelectric resistivity method in Pao Village, Tombolo Pao District, Gowa Regency. The configuration used for data collection in the field is the Wenner-Schlumberger configuration using four the number of lines. The result of research indicates that the first line average is founded in each layer which is suspected to occur in a layer of soil and igneous rock in the form of lava with 2.10 Ωm- 12.7 Ωm in resistivity value. In the second line, the average is founded wet soil, dry soil and igneous rock with 1.26 Ωm – 11.1 Ωm in resistivity value. The third line average is an established layer of soil and lava with 2.18 Ωm – 6.51 Ωm in resistivity value. The fourth line is suspected to occur layer of soil and lava with 1.59 Ωm – 8.50 Ωm in resistivity value and 1.25 m – 15.9 m in depth. It can be concluded that the first and fourth lines, based on the resistivity value, are generated to occur in a layer of soil. Igneous rocks are supported by topography, slup reaching 30o – 35o. Meanwhile, the second and third lines do not happen landslide potential because the resistivity results contain igneous rock. Still, the topography, vegetation, and slup are not the landslide-prone category.